Predation of Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) by Atopozelus opsimus (Hemiptera: Reduviidae) in Brazil - Dias, T. K. R. [UNESP]; Wilcken, C. F. [UNESP]; Soliman, E. P. [UNESP]; Barbosa, L. R.; Serrão, J. E.; Zanuncio, J. C. (Invertebrate Survival Journal, 2014)
The bronze bug Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) is an important pest of eucalyptus in several countries and the strategies for the integrated management of this insect in commercial plantations needs to be investigated. The predatory behavior of Atopozelus opsimus (Hemiptera: Reduviidae) on T. peregrinus is described. Adults of A. opsimus feed on nymphs and adults of the bronze bug and also present phytophagy. A. opsimus has potential as a natural enemy for the biological control of T. peregrinus.
Keywords: Atopozelus opsimus; Bronze bug; Predator